Stock de carbono contenido en la biomasa de las especies arbóreas de la parcela vi del arboretum “El Huayo” del centro de investigación y enseñanza forestal en puerto almendra, Iquitos, Perú-2022 - Campos Soria, Miguel Fernando (2025)
The carbon stock of tree species in plot VI of the CIEFOR (Central Forestry Institute) of the Faculty of Forestry Sciences, Puerto Almendra, was evaluated. Its floristic composition is made up of 602 individual trees, 119 tree species, and 33 botanical families, the Lecythidaceae family and the speciesEschweilera decolorans Sandwith are the most representative. A total of 195.45 t/ha of biomass and a carbon stock of 97.72 tC/ha were estimated. Eschweilera decolorans Sandwith with 37.65 t/ha of biomass and a carbon stock of 18.82 tC/ha, followed byAlchornea triplinervia (Spreng.) Müll. Arg. with 14.16 t/ha of biomass and a carbon stock of 7.08 tC/ha and Eschweilera rufifolia S. A. Mori It has 13.37 t/ha of biomass and a carbon stock of 3.79 tC/ha. The biomass and carbon stock maintain a 100% relationship between tree species. The statistical test tells us that it does not have a normal distribution and that is why the test is non-parametric Kruskal-Wallis, resulting in variation between the carbon storage present in the biomass and the tree species in plot VI. We conclude that the carbon stock will help maintain an ecological and environmental balance, regulating global warming in the atmosphere and promoting forest ecosystem services for the benefit of the main actors in being part of the carbon market.